Letter to editor: Incident depression increases medical utilization in Medicaid patients with hypertension. (January 2014) - Jerrell, Jeanette M; Tripathi, Avnish
<x xml:space="preserve">Abstract</x> Response to: Breunig IM, Roffman D, Tevie J, Shaya FT. Incident depression increases medical utilization in Medicaid patients with hypertension. Expert Rev Cardiovasc Ther 2015;13(1):111-118